PTSD Symptoms and Quality of Life in COVID-19 Survivors: The Mediating Effect of Resilience - Endang Widyorini; Margaretha Sih Setija Utami; Daniswara Augusta Wijaya; Benedicta Audrey Putri Trisnadewi; Josephine Ferren Heryanto (Philanthropy: Journal of Psychology, 2024)
Abstract. Quality of life (QoL) is a concept which aims to capture the well-being, whether of a population or individual, regarding both positive and negative elements within the entirety of their existence at a specific point in time. Many studies have found that PTSD symptoms can worsen the quality of life of COVID-19 survivors, and a high level of resilience can indicate a good quality of life for COVID-19, because a high level of resilience makes people able to rise from their worst condition. This study aimed to explain the mediating effect of resilience on the relationship between PTSD symptoms and the COVID-19 survivors’ quality of life. This study used a quantitative method, and 133 participants (mean age: 26.738; 75.2% female) were selected using a convenience sampling technique. Data analysis in this study used the IBM SPSS Statistics 26.0 program. PROCESS Macro 4.1 add-on by Hayes. Research results showed that in path a, PTSD symptoms significantly predicted resilience (β = -0.049; p = 0.001; LLCI = -0.072; ULCI = -0.020). In path b, resilience also significantly predicts quality of life (β = 2.156; p = 0.000; LLCI = 1.443; ULCI = 2.868). The direct effect of PTSD symptoms on quality of life shown in path c' is also significant (β = -0.387; p = 0.000; LLCI = -0.511; ULCI = -0.263) which gives higher results than the total effect (β = -0.493; p = 0.000; LLCI = -0.626; ULCI = -0.359). The results of the study show that PTSD symptoms had an antagonistic relationship, and resilience had a positive relationship with COVID-19 survivors’ quality of life. In addition, resilience was also found to significantly mediate the relationship between PTSD symptoms and COVID-19 survivors’ quality of life. COVID-19 survivors are advised to increase their resilience level to reduce the negative impact of PTSD symptoms on their quality of life.Keywords: COVID-19 survivors; PTSD symptoms;  quality of  life; resilience